Urban passenger transport energy saving and emission reduction potential: A case study for Tianjin, China. (15th September 2015) - Peng, Binbin; Du, Huibin; Ma, Shoufeng; Fan, Ying; Broadstock, David C.
Highlights: Potential to reduce urban passenger transport is projected between 2010 and 2040. Four scenarios reflecting different policy mixes are considered. The potential for energy conservation and emission reductions are obtained. Vehicle population regulation is most effective in energy saving and reducing overall GHG. Emission standards are the most effective measure to reduce pollutant emissions. Abstract: With rapid growth of the vehicle population, urban passenger transport in China is largely responsible for increases in energy consumption, greenhouse gas (GHG) emissions, and also atmospheric pollutants (NO x, CO, HC, PM). In this paper, we first develop an urban passenger transport energy saving and emission reduction potential evaluation model using the "Long Range Energy Alternatives Planning (LEAP)" tool; and then take Tianjin city as an empirical case to evaluate the reduction potential of final energy consumption, GHG emissions and pollutants emissions of Tianjin's urban passenger transport sector between 2010 and 2040 under four scenarios, i.e. BAU (business as usual) scenario, PP (the 12th five-year plan policy) scenario, CP (comprehensive policy) scenario and HP (hybrid policy of PP and CP) scenario. The results show that due to the public transport promotion, energy consumption and CO2 emissions in 2040 can be reduced by 22% and 22.6% in the PP scenario, compared to BAU. The largest reductions in energy consumption, CO2 and atmospheric pollutants emissions can be achieved under CP scenario, in which vehicle population regulation is the most effective to be implemented. Emissions standard regulation is the most effective measure to reduce atmospheric pollutant emissions in all the scenarios and green energy promotion is especially effective to reduce NO x and PM.